2011
DOI: 10.1111/j.1467-9922.2011.00672.x
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of /t, d/ and the Acquisition of Linguistic Variation by Second Language Learners of English

Abstract: This study investigated second language (L2) learners' acquisition of English /t, d/ deletion patterns in word-final consonant clusters, (a) focusing on how constraints such as grammatical conditioning and phonological environment affect deletion of /t, d/ in L2 acquisition and (b) determining the extent to which these L2 learners had acquired native-speaker-like patterns of deletion in ways that may be similar to patterns attested for first and second language acquisition in previous research. Seven native sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 37 publications
3
21
0
Order By: Relevance
“…However, when the category of consonant is analyzed by type of consonant, the findings are not as clear-cut. A few studies, notably Hansen Edwards (2011) for Mandarin Chinese L1 speakers of English and Guy (1991a) on AmE dialects, found liquids (/l/ for Guy 1991a) to favor deletion more than obstruents while Bayley (1996), also on research on Mandarin Chinese L1 speakers of English, found that obstruents and liquids both favored deletion more than other following environments. In the current study, a following liquid had the strongest effect on deletion with a VARBRUL weight of 0.734, followed by a following obstruent (0.571).…”
Section: Following Linguistic Environmentmentioning
confidence: 99%
See 4 more Smart Citations
“…However, when the category of consonant is analyzed by type of consonant, the findings are not as clear-cut. A few studies, notably Hansen Edwards (2011) for Mandarin Chinese L1 speakers of English and Guy (1991a) on AmE dialects, found liquids (/l/ for Guy 1991a) to favor deletion more than obstruents while Bayley (1996), also on research on Mandarin Chinese L1 speakers of English, found that obstruents and liquids both favored deletion more than other following environments. In the current study, a following liquid had the strongest effect on deletion with a VARBRUL weight of 0.734, followed by a following obstruent (0.571).…”
Section: Following Linguistic Environmentmentioning
confidence: 99%
“…These findings are consistent across a range of Englishes, including world Englishes (cf. Khan 1991;Bybee 2002;Lim & Guy 2005;Gut 2007;Hoffman & Walker 2010;Hansen Edwards 2011) and therefore appear to be universal, rather than variety-specific. A few studies, notably on York English (Tagliamonte & Temple 2005) and one study on pan-AmE dialects (Guy 1991aa) have found that liquids may have a stronger effect on deletion than obstruents, though it is unclear why this is the case.…”
Section: Research On /Td/ Deletionmentioning
confidence: 99%
See 3 more Smart Citations